Phospho-HDAC6 Gathers Into Protein Aggregates in Parkinson’s Disease and Atypical Parkinsonisms - Mazzetti, Samanta; De Leonardis, Mara; Gagliardi, Gloria; Calogero, Alessandra Maria; Basellini, Milo Jarno; Madaschi, Laura; Costa, Ilaria; Cacciatore, Francesca; Spinello, Sonia; Bramerio, Manuela; Cilia, Roberto; Rolando, Chiara; et al. (Frontiers in Neuroscience, 2020)
HDAC6 is a unique histone deacetylase that targets cytoplasmic non-histone proteins and has a specific ubiquitin-binding activity. Both of these activities are required for HDAC6-mediated formation of aggresomes, which contain misfolded proteins that will ultimately be degraded via autophagy. HDAC6 deacetylase activity is increased following phosphorylation on serine 22 (phospho-HDAC6). In human, HDAC6 localizes in neuronal Lewy bodies in Parkinson’s disease (PD) and in oligodendrocytic Papp-Lantos bodies in Multiple System Atrophy (MSA). However, the expression of phospho-HDAC6 in post-mortem human brains is currently unexplored. Here, we evaluate and compare the distribution of HDAC6 and its phosphorylated form in human brains obtained from patients affected by three forms of parkinsonism: two synucleinopathies (PD and MSA) and a tauopathy (Progressive Supranuclear Palsy, PSP). We find that both HDAC6 and its phosphorylated form localize with pathological protein aggregates, including -Synuclein-positive Lewy bodies in PD and Papp-Lantos bodies in MSA, and phospho-Tau-positive neurofibrillary tangles in PSP. We further find a direct interaction of HDAC6 with -Synuclein with proximity ligation assay (PLA) in Lewy bodies and in neuropil of PD patients. Taken together, our findings suggest that both HDAC6 and phospho-HDAC6 regulate the homeostasis of intra-neuronal proteins in parkinsonism.